2022
DOI: 10.1002/vzj2.20190
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and validation of soil water reflectometers

Abstract: In this study, we tested soil water reflectometers represented by the CS65x series soil water reflectometers. The objectives were to (a) quantify the sensing volume of the CS65x sensors, (b) evaluate common univariate and multivariate calibration models, and (c) assess the implications of using uncalibrated sensors. The support volume was determined by analyzing the response of the bulk dielectric permittivity to a changing amount of surrounding media in the radial and axial directions of the sensor. Calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
(123 reference statements)
1
14
0
Order By: Relevance
“…(1980), (b) calibration Equation (Ledieu et al., 1986), (c) calibration Equation (Evett et al., 2005), and (d) calibration Equation (Kargas & Soulis, 2019). All coefficients used in implementing Equations , and were derived from a separate laboratory sensor calibration in an independent study (Patrignani et al., 2022). The dashed line represents the 1:1 line…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(1980), (b) calibration Equation (Ledieu et al., 1986), (c) calibration Equation (Evett et al., 2005), and (d) calibration Equation (Kargas & Soulis, 2019). All coefficients used in implementing Equations , and were derived from a separate laboratory sensor calibration in an independent study (Patrignani et al., 2022). The dashed line represents the 1:1 line…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well known that the Topp model overestimates volumetric water content when used with soil water reflectometers in fine‐textured soils at moderate‐to‐high volumetric water contents (Caldwell et al., 2018; Evett et al., 2005; Kargas & Soulis, 2019). A recent laboratory sensor calibration study spanning nine soil textural classes collected across Kansas and Oklahoma shows that alternative univariate and multivariate linear models that account for bulk electrical conductivity and temperature effects can result in improved accuracy of soil water reflectometers (Patrignani et al., 2022). The authors suggested that these alternative linear models may be acceptable for network‐wide calibration of soil water reflectometers without the need for laborious and time‐consuming site‐specific sensor calibrations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations